23.0k views
5 votes
2) Use three functions above to evaluate the following: input f(x)=x-3_soupat f(3) = -3 p(0) = p(x)=0, x= function p(-4)= x/g(x) p(x)=5, x= 5 2 -3 f(x)=12, x=-4 f-3 = 12 -3 36207 g(-3)= p(1)= | p(3)= g(x)= -3, x = 95 = -3 p(x)=1, x= p(x)=2, x=​

2) Use three functions above to evaluate the following: input f(x)=x-3_soupat f(3) = -3 p-example-1
User Justmoon
by
5.5k points

1 Answer

4 votes

Answer:

f(3) = 3 - 3 --> f(3) = 0

f(x) = 12, x = 15 (because 15 - 3 would equal 12)

g(-3) = 2 (because in the chart for g(x), an x of -3 is 2)

g(x) = -3, x = 5 (because in the chart for g(x), a g(x) of -3 is an x of 5)

For the graph questions, p(0)= means that the 0 is the x integer and you must find the y when x=0

p(0) = 3

p(-4) = 5

p(1) = 3

p(x) = 1, x = 2

For the graph questions, p(x)=0 means that the 0 is the y integer and you must find the x when y=0

p(x) = 0, x = 2.5

p(x) = 5, x = -4

p(3) = -1

p(x) = 2, x = 1.5

User Shmakovpn
by
6.0k points